Greywater Reuse in a Sewered Area Design and Implementation at Research House - Kele, B.; Wolfs, Peter; Tomlinson, I.; Hood, B.; Midmore, D. (Lanfax Laboratories, 2005)
In Queensland, the Plumbing and Drainage Act (2002) is being amended to allow greywater reuse in sewered areas. The greywater must be treated and applied in a safe manner for both public and environmental health. The Queensland State Government has built, in Rockhanlpton, a Research House as part of their 'Towards Healthy and Sustainable Housing Research Project'. Research House was built using water-efficient infrastructure and has two rainwater tanks (total capacity 7 kL). The Central Queensland University (CQU) was asked to design a greywater treatment and reuse system for the House. The proposed design incorporates a backflow prevention device on the water mains entry to the house. The harvested storm water from the rainwater tanks will provide water for the hot-water system and laundry. This will reduce the amount of potable mains water required by the house and potentially provide softer water that should reduce the scaling in the hot-water system and require lower doses of detergents.The greywater from the laundry, shower, and vanity unit will be collected and primary treated in a deep vertical greasetrap. The primary treatment tank will have an overflow to the sewer. The primary treated greywater will be filtered and then used for subsurface irrigation. Research House has an established monitoring program that will be adapted to record the volumes of harvested stormwater and greywater reuse. Water quality parameters will be examined on a monthly basis. The proposed storm water reuse and greywater treatment and reuse plan is expected to reduce the amount of reticulated mains-supplied water used by Research House by approximately 45%.